Olfactometer-measured responses of Listronotus bonariensis (Kuschel) (Coleoptera: Curculionidae) to feeding-induced grass volatiles and conspecific frass as influenced by the weevil’s seasonality - Vereijssen, Jessica; van Tol, Rob; Rostás, Michael; van Koten, Chikako; Goldson, Stephen (Frontiers in Ecology and Evolution, 2024)
This contribution aimed to uncover the unique host plant-finding and spatial ecology of reproductive and diapausing Argentine stem weevil, Listronotus bonariensis, and its adaptive implications in Aotearoa-New Zealand pasture. Still-air two-armed olfactometers revealed the reproductive and diapausing L. bonariensis preferences for plant and weevil-derived volatiles. Winter-collected diapausing weevils were strongly attracted to host plant feeding damage by conspecifics and their frass. Such attraction disappeared when 20 stem weevils were added to the damaged ryegrass. This suggests that L. bonariensis on a damaged host plant above a certain density causes repellency probably avoiding over-exploitation of the host plant. Neither the weevils’ sex nor related physiological condition were found to impart any significant effects. Volatile organic compound (VOC) analysis showed that phenylacetaldehyde was the only de novo synthesised herbivore-induced volatile compound found resulting from diapausing L. bonariensis feeding damage. This study therefore found that the seasonal behaviour of L. bonariensis was very closely related to that of the rice water weevil Lissorhoptrus oryzophilus and its very similar responses to phenylacetaldehyde. In both cases the compound attracts spring populations (emerging from diapause) to their host plants and conspecifics. Thereafter, as with L. oryzophilus, L. bonariensis similarly on becoming reproductive, its sensitivity to phenylacetaldehyde ceases. Such close connection between L. bonariensis and L. oryzophilus seasonal responses to phenylacetaldehyde therefore greatly reenforces the concept of evolved L. bonariensis behaviour in its native range as being relict behaviour in New Zealand’s grassland ecosystem.